2018
DOI: 10.1038/s41398-018-0208-5
|View full text |Cite
|
Sign up to set email alerts
|

PSD95 and nNOS interaction as a novel molecular target to modulate conditioned fear: relevance to PTSD

Abstract: Stimulation of N-methyl-D-aspartic acid receptors (NMDARs) and the resulting increase of nitric oxide (NO) production are critical for fear memory formation. Following NMDAR activation, efficient production of NO requires linking the 95 kDa postsynaptic density protein (PSD95), a scaffolding protein to neuronal nitric oxide synthase (nNOS). A variety of previously studied NMDAR antagonists and NOS inhibitors can disrupt fear conditioning, but they also affect many other CNS functions such as motor activity, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…In this study, a single dose of ZL006, a small-molecule inhibitor of PSD95/nNOS, attenuated escalation of attack behavior in the resident–intruder test at a dose that did not affect locomotor activity. To our knowledge, this is the first study to demonstrate that targeting PSD95/nNOS with ZL006 attenuates attack behavior induced by SI, thereby adding to the evidence for ZL006 as a potential treatment for various neurological disorders (Cai et al 2018b ; Doucet et al 2013 ; Li et al 2018 ; Qin et al 2019 ). Notably, we demonstrated that the effect of ZL006 on attack behavior was mediated via suppression of production of NO.…”
Section: Discussionmentioning
confidence: 61%
“…In this study, a single dose of ZL006, a small-molecule inhibitor of PSD95/nNOS, attenuated escalation of attack behavior in the resident–intruder test at a dose that did not affect locomotor activity. To our knowledge, this is the first study to demonstrate that targeting PSD95/nNOS with ZL006 attenuates attack behavior induced by SI, thereby adding to the evidence for ZL006 as a potential treatment for various neurological disorders (Cai et al 2018b ; Doucet et al 2013 ; Li et al 2018 ; Qin et al 2019 ). Notably, we demonstrated that the effect of ZL006 on attack behavior was mediated via suppression of production of NO.…”
Section: Discussionmentioning
confidence: 61%
“… 98 Therapeutic approaches have been proposed to disrupt PSD-95/NMDAR complex to ameliorate pathological changes. 99–101 Meanwhile, our results showed increased PSD-95 expression was closely associated with improved learning and memory and locomotor activity. It is possible that increased PSD-95 serves as a compensatory mechanism for its loss in formation of abnormal complexes and to enhance its synaptic function, as evidenced in studies in which increased PSD-95 correlates with its protective effects in Alzheimer's disease and Parkinson's disease animal models.…”
Section: Discussionmentioning
confidence: 68%
“…We and others have previously emphasized the potential for targeting the nNOS/PSD-95 interaction for the pharmacological treatment of schizophrenia, depression, and other mental disorders [ 1 , 14 , 78 , 79 ]. The findings from the present study support this assertion and indicate a potential for directly targeting (i.e.…”
Section: Discussionmentioning
confidence: 99%